Configurations of tunnel deceleration area. Issue 1 (July 2021) - Zhang, Yanhong; Fan, Yunlong; He, Jianbin; Tian, Jialei; Ma, Xiangnan; Yuwen, Weiyuan; Tan, Yuanxin
Abstract: The deceleration area of the tunnel has always been the place where accidents occur frequently. Recently published statistics on tunnel accidents showed that 42 percent of which are rear-end collisions. The main reason lies on the luminance difference between the inside and the outside parts of the tunnel. The inside part of the tunnel is much darker than that of the outside part, which results in a "sight shock" and shortage of clear sight for drivers at the tunnel portal. If the tunnel deceleration area is not long enough and the vehicle is at a high speed, rear-end collisions will most likely occur at this area. Therefore, it is important to design the deceleration area of the tunnel in order to avoid rear-end collisions. This paper explains the cause of rear-end collision at deceleration area from the principles of physics and physiology. The mathematical relations among the speed, time and distance of trucks and cars entering the tunnel are given from the mathematical point of view. Finally, this paper puts forward the design idea and reasonable suggestions for the configuration of tunnel deceleration area.